Comparative Analysis of Penalty Clauses in Civil Contracts: Enhancing Legal Certainty and Substantive Justice in Indonesian Law - Lely Sulthoniah; Djumikasih; Yenny Eta Widyanti (The Islamic Education and Multiculturalism Foundation, 2025)
Abstract Penalty clauses in civil contracts serve as a preventive mechanism against breach of contract and as a legal protection tool for the aggrieved party. However, the Indonesian Civil Code (KUHPerdata) does not explicitly regulate such clauses, resulting in legal uncertainty and inconsistent judicial practices. This study aims to comparatively analyze the regulation and implementation of penalty clauses in Indonesia, the United Kingdom (via the concept of liquidated damages), and Germany (through Strafklauseln). Employing normative, conceptual, case study, and comparative approaches, the findings reveal that Indonesia’s legal framework remains weak and heavily reliant on judicial discretion, in contrast to the more structured and proportionate approaches found in the UK and Germany. The study recommends a reformulation of Indonesia’s legal framework governing penalty clauses to strengthen legal certainty and ensure substantive justice. The novelty of this research lies in its cross-system legal analysis and emphasis on the need for contractual justice reform in Indonesian civil law. Keywords: Penalty Clause, Breach of Contract, Justice, Contract Law, Legal Comparison